Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 6 - Logarithmic Functions - Chapter Review Exercises: 2

Answer

$g^{-1}(t) = -\frac{t-6}{2}$

Work Step by Step

$g(t) = -2t+6$ Let $g(t) = y$ $y = -2t + 6$ Swap the variables $t$ and $y$ and then solve for $y$ to find the inverse: $t = -2y + 6$ $t - 6 = -2y$ $y = -\frac{t-6}{2}$ $g^{-1}(t) = -\frac{t-6}{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.